1990
DOI: 10.1111/j.1467-8624.1990.tb02876.x
|View full text |Cite
|
Sign up to set email alerts
|

The Principle of Mutual Exclusivity in Word Learning: To Honor or Not to Honor?

Abstract: According to Markman and Wachtel, children assume that nouns pick out mutually exclusive object categories, and so each object should have only one category label. While this assumption can be useful in word learning, it is not entirely reliable. Therefore, children need to learn when to and when not to make this assumption. 6 studies examined whether knowledge about hierarchical organization of categories and about cross-language equivalents for object labels can help children limit their use of this assumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 37 publications
1
63
0
Order By: Relevance
“…When providing translations, parents often explicitly mark that they are providing a label in the other language, suggesting that they may be trying to help children organize their language knowledge. A potential consequence of this explicit talk may be that bilingual children develop language learning biases, such as mutual exclusivity, differently compared to monolingual children (Au & Glusman, 1990). …”
Section: Discussionmentioning
confidence: 99%
“…When providing translations, parents often explicitly mark that they are providing a label in the other language, suggesting that they may be trying to help children organize their language knowledge. A potential consequence of this explicit talk may be that bilingual children develop language learning biases, such as mutual exclusivity, differently compared to monolingual children (Au & Glusman, 1990). …”
Section: Discussionmentioning
confidence: 99%
“…We chose this contextual cue for two reasons. First, there is ample evidence that the phonological structure of words (including syllable length and phonotactics) aids in resolving ambiguities in word and sentence meanings (Au & Glusman, 1990; Durieux & Gillis, 2001; Kelly, 1996). Additionally, learners are successful at using phonological cues and word structure in statistical learning (Escudero et al, 2015; Lew-Williams & Saffran, 2012; Sahni, Seidenberg, & Saffran, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Children believe that labels for objects are mutually exclusive, that is, a given object can only have one name (Markman, 1989; Woodward, 2000 for discussion). Moreover, the tendency for this assumption to influence children’s naming behavior increases during the preschool years (Au & Glusman, 1990; Merriman & Bowman, 1989), and some have suggested that it is a heuristic that children learn to use as they get older (MacWhinney, 1991). Others have proposed that the constraint may be a default strategy that children use when other options are not available (Merriman & Bowman, 1989; Markman, 1992).…”
mentioning
confidence: 99%
“…Some studies report less reliance of bilingual children on ME than matched monolinguals (Davidson, Jergovic, Imami, & Theodos, 1997; Davidson & Tell, 2005; Yow & Markman, 2007) and others find no difference (Au & Glusman, 1990; Frank & Poulin-Dubois, 2002; Merriman & Kutlesic, 1993). Although bilingual children are familiar with having two names for a particular object, it appears that the ME constraint does not apply if the words come from different languages, even for monolingual children (Au & Glusman, 1990). Thus, there may be no difference between monolingual and bilingual children in adopting this strategy for words in the same language.…”
mentioning
confidence: 99%